Prevalence of Cryptosporidium spp., Enterocytozoon bieneusi, Encephalitozoon spp. and Giardia intestinalis in wild, semi-wild and captive orangutans (Pongo abelii and Pongo pygmaeus) on Sumatra and Borneo, Indonesia. - Mynářová, Anna (Jihočeská univerzita, 2016)
The prevalence and diversity of Cryptosporidium spp., microsporidia and Giardia intestinalis in orangutans (Pongo abelii and Pongo pygmaeus) at seven different sites on Sumatra and Kalimantan were described using molecular methods. Out of the 298 examined animals, 33 were positive for the tested parasites at least once during the study. Microsporidia(Encephalitozoon spp. and Enterocytozoon bieneusi) were detected in orangutans for the first time and molecular data were obtained on Cryptosporidium spp. and G. intestinalis in this host.
Prevalence of Cryptosporidium spp., Enterocytozoon bieneusi, Encephalitozoon spp. and Giardia intestinalis in wild, semi-wild and captive orangutans (Pongo abelii and Pongo pygmaeus) on Sumatra and Borneo, Indonesia.